Management innovation of Islamic education on the basis of life skills competency (a study case of pesantren Agro Nur El-Falah Salatiga) - Taufiqurrahman, Taufiqurrahman; Giyoto, Giyoto (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
Pesantren (Islamic boarding school), as the oldest Islamic educational institution in Indonesia, requires well-organized management in order to successfully lead the students to build an Islamic competency and also excel in the fields of science and technology. The management of Pesantren should be adjusted towards the demands of the era and the needs of students after completing their education at Pesantren while maintaining Islamic competence as a characteristic of Islamic boarding schools. A pesantren providing a basis for life skills in Salatiga is Agro Nur El-Falah Islamic Boarding School. The purpose of this research is to analyze in detail the Management Innovation of the Agro Nur el-Falah Islamic Boarding School in providing life skills competencies to the students. The researcher uses a qualitative descriptive method with the aim of describing a situation objectively in accordance with the description of the situation. Therefore, this research will further describe life skills-based Islamic education management innovation at Agro Nur El-Falah Islamic Boarding School Salatiga. The results of this research indicate that Islamic education at Agro Nur El-Falah Islamic Boarding School has successfully provided not only Islamic knowledge as a key feature of Islamic education, but also life skills competencies to the students.